Engineering the Electrochemical Reduction of Carbon and Silica in Molten CaCl2: Manipulation of the Electrolytic Products. Issue 4 (1st January 2019) - Zhao, Haijia; Xie, Hongwei; Zhou, Xianbo; Qu, Jiakang; Zhao, Zhuqing; Song, Qiushi; Ning, Zhiqiang; Xing, Pengfei; Yin, Huayi
Abstract : Silicon (Si)/carbon (C) composites, silicon carbide (SiC), and Si films are electrochemically prepared in molten CaCl2, and the interaction of Si with C is systematically analyzed. Further, the effects of the cell voltage of electrolysis and the formation of SiO2 and C on the electrolytic products were studied. Electrolytic SiC can be identified as the thermodynamically favored product because the Gibbs free energy of formation of SiC is negative at 850°C. The electrolysis of the C/SiO2 mixture prepared by the mechanical mixing of the C (i.e., graphite or sugar-derived C) and SiO2 powders resulted in the generation of the thermodynamically unfavored Si/C composite. Further, the thermodynamically favored SiC was obtained by the electrolysis of SiO2 coated with sugar-derived C. Moreover, the electrodeposition of Si films onto both graphite foils and C fibers was conducted in molten CaCl2, and the boundary of the electrolytic Si film/C substrate was obtained using scanning electron microscopy and X-ray photoelectron spectroscopy. Overall, the contact area between SiO2 and C is required for engineering the electrolysis to obtain products such as the Si/C composites, SiC, and Si films.